Structure and large-scale environment of galaxy pairs in the S-PLUS DR4 - Cerdosino, María Candela (2024)
In this paper, we use photometric data from the Southern Photometric Local Universe Survey Data Release 4 survey to identify isolated galaxy pairs and analyse their characteristics and properties. Our results align with previous spectroscopic studies, particularly in luminosity function parameters, suggesting a consistent trait among galaxy systems. Our findings reveal a high fraction of red galaxies across all samples, irrespective of projected distance, velocity difference, or luminosity ratio. We found that the proximity of a neighbour to its central galaxy influences its colour due to environmental effects. We also found that central and neighbour have different behaviours: central galaxies maintain a stable red colour regardless of luminosity, while neighbour colours vary based on luminosity ratios. When the central is significantly brighter, the neighbour tends to be less red. According to our division in red, blue, and mixed pairs, we found evidence of galactic conformity. The red pair fractions increase in closer pairs and in pairs of similar luminosity, indicating shared environments promoting red galaxy formation. Analysing local density, the expected colour-density relation is of course recovered, but it is strongly determined by the stellar mass of the pair. In denser environments, the red pair fractions increase, blue pairs decrease, and for the mixed pairs it depends on their stellar mass: more massive mixed pairs decrease their fraction, whereas the less massive ones increase it. These results shed light on the intricate relationship between galaxy pairs, their characteristics, and environmental influences on colour, providing insights into their evolutionary histories.